The Role of the Portal to English Syllabuses in Developing the Language Skills of Preparatory School Students - Telal Mirghani Khalid (English Education Department at FKIP Nommensen University, 2021)
Teaching English through an effective curriculum enables EFL students to establish and achieve effective communication. The study aims to investigate issues affecting EFL students by learning English and discussing the role of Portal to English syllabuses in developing the language skills of Qatari school students. Research has harmonized the analytical approach. The required information was collected from a questionnaire distributed to twenty (20) Qatari EFL teachers in preparatory schools. Then, the data was analyzed according to the SPSS system. The results show that the Portal course syllabuses of Qatari preparatory schools introduce language activities that promote oral interaction in addition to the previous syllabuses. This current syllabus motivates students and builds a good understanding of learning English and improving language skills. The textbooks emphasize the use of English in social media and in the practice of Qataris customs and traditions. Portal lessons emphasize oral interactions with group work and discussions. Vocabulary and writing activities are presented and tested in many units in the Portal course series.